2019
DOI: 10.1002/nag.2928
|View full text |Cite
|
Sign up to set email alerts
|

One‐dimensional self‐weight consolidation with continuous drainage boundary conditions: Solution and application to clay‐drain reclamation

Abstract: Summary Traditional consolidation theories cannot provide good predictions of consolidation settlement in land reclamation because of their assumptions that the influence of soil's self‐weight is often neglected, and the drainage boundary is considered as fully pervious/impervious. In view of these limitations, an analytical solution is derived for one‐dimensional self‐weight consolidation problems with a continuous drainage boundary using the finite Fourier sine transform method. Following the classical Terza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…In the Terzaghi consolidation theory, the boundary surface is just assumed to be pervious or impervious, which results in the boundary condition ( u (0, t ) = 0) being inconsistent with the initial condition ( u ( z ,0) = p ). Therefore, as demonstrated in Figure , this article introduces the continuous drainage boundaries as follows: u()0,t=peitalicbt=peBTv, u(),2ht=peitalicct=peCTv, where b , c , B , and C represent the interface parameters related to the properties of adjacent soil layers and reflect the drainage properties of the drainage boundaries, and they can be obtained through experimental simulation or engineering measurement inversion. Note that B and C are the normalized expressions of b and c , respectively, and the normalized time factor T v = C v t / h 2 .…”
Section: Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Terzaghi consolidation theory, the boundary surface is just assumed to be pervious or impervious, which results in the boundary condition ( u (0, t ) = 0) being inconsistent with the initial condition ( u ( z ,0) = p ). Therefore, as demonstrated in Figure , this article introduces the continuous drainage boundaries as follows: u()0,t=peitalicbt=peBTv, u(),2ht=peitalicct=peCTv, where b , c , B , and C represent the interface parameters related to the properties of adjacent soil layers and reflect the drainage properties of the drainage boundaries, and they can be obtained through experimental simulation or engineering measurement inversion. Note that B and C are the normalized expressions of b and c , respectively, and the normalized time factor T v = C v t / h 2 .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…In this comparison, a one‐stage ramp load with T c = 0.2 as shown in Figure is exerted onto the surface of the soil. It was explained from previous studies that the interface parameters B and C reflect the drainage capacities of the top and bottom surfaces of the soil, respectively, and the larger the values of these interface parameters, the stronger the drainage capacity of the corresponding boundary. It is also found from Figure that with the gradual increase of interface parameters B and C , the top and bottom surfaces of the soil are increasingly able to drain water, and when the interface parameters B and C become large enough (ie, B = C = 800 in this case), the distribution of the excess pore‐water pressure obtained by the present solution is consistent with that calculated by Conte and Troncone's solution .…”
Section: Comparative Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [39] showed that the continuous boundary has good applicability and extends to the semi-analytical solution of one-dimensional consolidation of unsaturated soil. Feng et al [40] established the one-dimensional consolidation equation for the continuous drainage boundary and studied the contribution of a soil's self-weight stress. Sun et al [41] established a general analytical solution for the one-dimensional consolidation of soil for the continuous drainage boundary under a ramp load.…”
Section: Introductionmentioning
confidence: 99%